Pengembangan Wisata Religi Petilasan Nyai Mas Gamparan Gong Suprayoga dan Gambang Caning Desa Tanjungsari Kecamatan Pabuaran Kabupaten Serang - Gatot Hartoko; Eli Apud Saepudin; Jihan Lutfiah (WINDRADI: Jurnal Pengabdian Masyarakat, 2023)
The name Nyaimas Gamparan is still somewhat foreign to the ears of Banten residents Nyaimas Gamparan is a descendant who was born in Surakarta. But his work in fighting the colonizers is worth remembering. Nyaimas Gamparan's rebellion against the Dutch rejected the culturrstelsel forced planting system that would be implemented in Banten in 1883. Nyaimas Gamparan firmly sounded the drums of war with the Dutch. The Dutch troops, who were almost defeated by Nyaimas Gamparan's troops at that time, quickly organized a strategy to pit the people against each other. Because of this, Nyaimas Gamparan's hiding place was known and surrounded by the colonial troops so that the strategy and secrecy and hiding place or ascetic Nyaimas Gamparan leaked into the hands of the Dutch, so that Nyimas Gamparan was besieged when fighting against the Dutch. Until now in the Banten region the tomb of Nyaimas Gamparan is unknown. However, the place of patilasan or gathering place to organize the strategy of war against the Dutch is in Kadaung Village, Tanjung Sari Village, Pabuaran District, Serang Regency. The purpose of this Community Service activity is to develop religious tourism through group 60 KKM activities with Bina Bangsa University Lecturers and the Education and Culture Office of Serang Regency.